Phytotherapy in pediatrics: the production of knowledge and practices in Primary Care - Cynthia de Jesus Freire; Lucas Roberto da Silva Barbosa; João Gomes da Costa; Renata Guerda de Araújo Santos; Aldenir Feitosa dos Santos
ABSTRACT Objective: To demonstrate the use of phytotherapy as a therapy adopted in the context of Primary Care to Childhood. Method: Observational and analytical field research, with quantitative-qualitative approach. A semi-structured survey was used on socio-demographic and ethnopharmacological variables, audio interview and daily observation. Results: The production of knowledge about phytotherapy constitutes a family heritage, but incorporated data resulting from the daily experiences shared by the community. The main factors were: easy access to this resource, high costs of conventional treatment, difficulty in accessing medical services and belief in the power of plants. The attributed meanings were: prevention and treatment of injuries, rescue of memory and of experiences, factor integrative with nature and aggregative among members of the community. Final considerations: Rescuing this tradition brings a new meaning to health care.